O nekotorych osobennostjach definicij ponjatij terrorizm i terrorističeskij akt - Edilova, M. M. (Chabaršy. Dintanu serijasy, 2020)
The article deals with a complex, multifaceted phenomenon - terrorism, which is a serious challenge to modern world civilization, the processes of globalization. Various definitions of terrorism are given, a community of these definitions is shown, which is associated with violence, in which terrorism is characterized as a socially dangerous phenomenon of public life, deserving of severe condemnation and struggle from the whole world community. The authors note that modern terrorist groups have at their disposal a large arsenal of informational, technological, psychotropic and other methods for directly or indirectly affecting a "potential" enemy. The main types and types of terrorism are analyzed - worldview, political, religiously-motivated, criminal, etc., their general and distinctive features are revealed. The authors dwell in detail on the problems of a terrorist act, revealing its criminal, antisocial essence, which is the result of terrorist activity. The structure of a terrorist act is shown, which includes three elements: a terrorist, his victim (target of attack) and persons who are the target of influence. Attention is also paid to methods of combating terrorism, of which religious education is effective, since a person who knows religion well will never join the ranks of terrorists.